Dangerous Worldview and Perceived Sociopolitical Control: Two Mechanisms to Understand Trust in Authoritarian Political Leaders in Economically Threatening Contexts - Torres-Vega, Laura C.; Ruiz, Josefa; Moya, Miguel (Frontiers in Psychology, 2021)
In this research we analyzed the relationship between threatening economic contexts (i.e., undergoing the economic crisis and having low socioeconomic status) and trust in authoritarian ideologies and leaders, regardless of the left-right political axis. Based on two theoretical approaches (i.e., the dual-process model and the compensatory control model), we argue that this relationship is mediated by dangerous worldview and low perceived sociopolitical control. We conducted two correlational studies with samples of the general population. In Study 1 (N = 185), we found that perceived threat from the economic crisis and low socioeconomic status were correlated with a higher dangerous worldview, which resulted in a more authoritarian ideology (i.e., authoritarianism) and finally in greater trust in an authoritarian political leader. In Study 2 (N = 413), we replicated the findings of Study 1 and demonstrated that low perceived sociopolitical control was associated with higher authoritarianism. Moreover, low perceived sociopolitical control partially mediated the relationship between dangerous worldview and authoritarianism. Overall, our results show that two economically threatening contexts (i.e., the economic crisis and low socioeconomic status) promote authoritarianism and trust in authoritarian leaders (with unspecified political orientation) through psychological processes (i.e., perception of the social world and perceived control). These results are useful to understand and combat the rise of authoritarianism in our societies during financially difficult times such as economic crises.